The Effect of Small Organic Anions on Aggregation and Shape Change of Rabbit Platelets - Anderson, Esther R; Foulks, J G (Thrombosis and Haemostasis, 1978)
Sufficient concentrations of small organic anions inhibited ADP- or 5-HT-induced shape change and aggregation in rabbit PRP diluted with isotonic salt solutions. Both effects were concentration-dependent and varied with the size of the hydrocarbon chain. Carboxylate and sulfonate anions of corresponding size produced a similar degree of interference with aggregation but carboxylates were somewhat more effective than sulfonates in impairing shape change. The inhibitory effect of these anions was not potentiated by a phosphodiesterase inhibitor and therefore was not attributable to adenylate cyclase activation.The inhibition of shape change by both series of anions was enhanced at acid pH, an effect which was greater with carboxylates than with alkyl sulfonates. The pH dependence of shape change on the alkaline side of the optimum range was unaffected by either type of anion. These results show that organic anions exert their inhibitory effects on platelets at least in part at the external platelet surface, and that their effects can be influenced by the degree of dissociations of protonatable membrane groups. Hence, surface negative charge and hydrophobic interactions both play an important role in platelet functional responses and their modification by organic anions. The inhibition of aggregation by these anions was opposed by the addition of calcium. Kinetic analysis indicated that both activation of aggregation by Ca++ and inhibition of aggregation by organic anions involved more than one site or mechanism of action. The more sensitive inhibitory effect was surmounted by increased Ca++ concentrations without apparent alteration in the affinity of Ca++ binding sites and competitive antagonism was evident only at high concentrations of organic anions. A simple model to account for these effects is proposed.